253 C-REACTIVE PROTEIN:ADIPONECTIN RATIO: A NOVEL DIAGNOSTIC BIOMARKER OF THE METABOLIC SYNDROME. (1st January 2006) - Miguelino, E. S.; Devaraj, S.; Jialal, I.
Abstract : Metabolic syndrome (MS) is a common disorder, comprising a constellation of risk factors including abdominal obesity, dyslipidemia, hypertension, and impaired fasting glucose levels and is associated with increased cardiovascular mortality. Inflammation plays a crucial role in atherosclerosis. Several prospective studies have demonstrated that high levels of C-reactive protein (CRP) predict cardiovascular events. CRP levels are elevated in subjects with MS. Abdominal obesity is a predominant feature of MS. The adipose tissue secretes an anti-inflammatory adipocytokine, adiponectin, which is decreased in subjects with MS. Thus, the aim of the study was to determine if the CRP:adiponectin ratio will provide a better discriminant for MS than CRP alone. Age-matched subjects without MS (controls) and > 3 features (MS-by NCEP criteria), were recruited ( n = 68/group). Following informed consent, fasting blood was drawn. CRP levels were measured by automated immunoassay and adiponectin was measured by ELISA, both assays with inter- and intraassay CVs of < 7%. CRP levels were significantly elevated in subjects with MS [median and interquartile range MS: 3.9 mg/L (2.9, 5.7); C: 1.3 mg/(0.6, 2.8), p < .001] while adiponectin levels were significantly lower in MS subjects [median and interquartile range MS: 7.8 (5.6, 9.5); C: 8.2 mg/L (7.3, 9.1), p < .05]. Furthermore, there was a significant increase in CRP:adiponectin ratio in MS [median and interquartile range MS: 0.56 (0.29, 0.87); C:0.17 (0.08, 0.39); p < .001]. The CRP:adiponectin ratio was significantly better in predicting MS (89%, p < .02) than either CRP alone (67%) or adiponectin alone (31%). Furthermore, the CRP:adiponectin ratio correlated better with multiple features of MS (waist, low HDL, glucose, blood pressure, etc) than CRP alone (r = .81 for ratio and r = .66 for CRP, p < .01). Thus, the CRP:adiponectin ratio may provide a better objective measure for diagnosis of MS and monitoring therapeutic manipulations in the clinical setting.